2017
DOI: 10.4103/jhrs.jhrs_15_17
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation induction using clomiphene citrate using stair – Step regimen versus traditional regimen in polycystic ovary syndrome women – A randomized control trial

Abstract: Objective:To determine the efficacy of the stair-step protocol (SSP) using clomiphene citrate (CC) in patients with polycystic ovary syndrome (PCOS) and compare it with traditional regimen.Design:This was randomized control trial.Setting:Infertility Clinic.Patient(s):Sixty infertile PCOS women.Intervention(s):Patients were randomized into the study (SSP – 30 patients) and control group (traditional protocol – 30 patients). In the SSP, patients were treated with CC 50 mg/day for 5 days and in nonresponsive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Jones et al reported a significant increase in the number of follicles in the SSP group, with mean values of 2 in SSP and 1 in CC (4) . Agrawal et al found the highest number of follicles and the largest follicle size in the SSP group (12) . However, our results do not align with those of Pourhoseini et al, who found no significant differences between the two groups in terms of the number of medium, large, or total follicles (pvalues of 0.288 for all) (13) .…”
Section: Discussionmentioning
confidence: 95%
“…Jones et al reported a significant increase in the number of follicles in the SSP group, with mean values of 2 in SSP and 1 in CC (4) . Agrawal et al found the highest number of follicles and the largest follicle size in the SSP group (12) . However, our results do not align with those of Pourhoseini et al, who found no significant differences between the two groups in terms of the number of medium, large, or total follicles (pvalues of 0.288 for all) (13) .…”
Section: Discussionmentioning
confidence: 95%